DEVELOPMENT OF TRAINING PROFESSIONAL PRACTICE TRAINING (PPK) FOR TEACHERS TO IMPROVE GUIDANCE COMPETENCE IN STUDENTS OF PPK S1 - Kapraja Sangadji (EDU SCIENCES JOURNAL, 2020)
The purpose of this study is to facilitate teacher tutors to fully understand the concept of teacher professional practice, while honing their knowledge, attitudes, and skills, as well as guiding procedures for teacher tutors in improving pedagogical competencies of undergraduate students in managing quality learning. The development of PPK training for tutor teachers in the form of modules refers to the Rowntree model. The Rowntree model is a development model specifically aimed at developing learning materials which have three main stages namely planning materials, preparing for writing, writing and re-writing. PPK training materials can have a positive influence and have a significant impact on teacher tutoring effectively in mentoring student students. This will be seen from the improvement of teacher tutor competence in mentoring PPK students. Teacher tutoring competency can improve learning performance and contribute to the ability and willingness in collaboration for self-development and contribute to the development of student mentoring